2018
DOI: 10.1186/s40069-018-0313-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of CFRP Reinforced Concrete Members Utilizing Fuzzy Technique

Abstract: Aging and structural deterioration under severe environments are major causes of damage in reinforced concrete (RC) structures, such as buildings and bridges. Degradations such as concrete cracks, corrosion of steel, and deformation of structural members can significantly degrade the structural performance and safety. Therefore, effective and easy-to-use methods are desired for repairing and strengthening such concrete structures. Various methods for the strengthening and rehabilitation of RC structures have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In the recent decade, soft computing has become one of the most well-known intelligence techniques due to the lower cost and time consumption in different engineering sciences (Cai et al, 2019;Chung et al, 2018;Heo et al, 2018;Ryu et al, 2020;Shafaei and Khayati, 2020). Combining fuzzy logic with neural networks presents adaptive network-based fuzzy inference systems (ANFIS) to determine the superlative relationship among the input and output parameters in various processes.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, soft computing has become one of the most well-known intelligence techniques due to the lower cost and time consumption in different engineering sciences (Cai et al, 2019;Chung et al, 2018;Heo et al, 2018;Ryu et al, 2020;Shafaei and Khayati, 2020). Combining fuzzy logic with neural networks presents adaptive network-based fuzzy inference systems (ANFIS) to determine the superlative relationship among the input and output parameters in various processes.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, FRP wrapping method is considered to be the most cost-effective and simple way to improve the load-carrying capacity, ductility, and shear strength of deteriorated concrete members (Almusallam et al, 2018;Bonacci & Maalej, 2001;Chung et al, 2018;Kim et al, 2013;Lu et al, 2005;Truong et al, 2017;Youm et al, 2006). The FRP surface wrapping method gives confinement effect and stiffness enhancement to resist seismic loading.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the excellent material properties of Carbon Fiber Reinforced Polymer (CFRP), this material has been widely applied in the reinforcement of bridge structures (Siddika et al, 2019;Zhuang et al, 2018;Bocciarelli et al, 2018;Lepretre et al, 2018;Chataigner et al, 2018). Many scholars have carried out many investigations on the mechanical properties and failure mode of CFRP reinforced beams (Hawileh et al, 2014;Gallego et al, 2017;Chung et al, 2018). Studies have shown that the failure modes of CFRP-reinforced structures are often manifested as various types of debonding failure of CFRP-concrete interface (Zhang et al, 2017;Zeng et al, 2018;Rukavina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%